What’s Going on Out There? An exploration of K–12 PE Curricular Models and Content Taught in Public Schools - Hodges, Michael; Laughlin, Michael; Brusseau, Timothy (The Physical Educator, 2018)
Little is known about which curricular models and activity units are being taught in public schools. This exploratory study examined the K–12 physical education (PE) content and curricular models being implemented. Supervisors of PE recruited from one northeastern state participated in a 25-item questionnaire. Descriptive statistics and frequencies were calculated. Sixty-nine of 92 questionnaires were usable and included in the data analysis. Findings suggest that few districts were using a curricular model at the elementary (K–5) level (27%). Another common response of adopted curricular models at the elementary level was Movement Education (17.6%). At the secondary level, No Model (35%) and Fitness Education (25.6%) were common responses. Specific units such as volleyball, basketball, and weight training yielded the highest responses, while field hockey, golf, archery, lacrosse, and tennis yielded the fewest responses. The findings suggest that K–12 PE curricula may not reflect current trends and mandates. The key determinants could be a lack of curricular model use and heavy reliance upon activities known to present challenges toward standards-based education (i.e., softball). Perhaps K–12 PE and PE preparation programs can connect to effectively articulate a curriculum, and adopt and train on curricular approaches aiming to increase teacher effectiveness and reach national standards.Subscribe to TPE
Number: 5
Keywords: Content; Curricular Models; PETE; Units; dept.hms